Digestibilidade aparente da quirera e do farelo de arroz incluídos em distintas concentrações em rações para tilápia do Nilo - Brisqueleal, Jean Carlos Pianta (2024)
This study aimed to evaluate the apparent digestibility coefficients and amino acid coefficients of rice grits and rice bran, when included in different concentrations (6%, 12%, 18%, 24% and 30%), in diets for juveniles. of Nile tilapia. Chromium-II oxide was used as an inert additive for feed. 480 specimens of tilapia with an average weight of 510 grams were used for the experiment with rice grits as a reference ingredient and an average weight of 564 grams for the experiment with rice bran, both experiments lasted 21 days each, 7 days for fish acclimatization in the tanks and 14 days for feces collection. To evaluate the tested ingredient, the fish were randomly distributed in a completely randomized design, consisting of six treatments (five inclusion levels and one reference), with each treatment having four replications. The results demonstrated a higher dry matter of 18% when including rice grits and 6% using rice bran. The highest protein apparent digestibility coefficient (ADC) was 24% for chickpeas and 6% for bran. However, in relation to the energy CDA, the level of 24% for both ingredients stands out. In relation to amino acids, the 30% inclusion level presented the best average results with rice bran and the 18% level for rice bran stands out. Thus highlighting the importance of rice derivatives in formulating diets for Nile tilapia, as well as the importance of testing new levels of inclusion with the aim of lowering production costs and taking advantage of highly nutritious food derivatives with good digestibility.